Application of the Positive Reinforcement to Enhance the Learnability of EFL Learners - Basnet, Bhavana (Journal of Durgalaxmi, 2022)
The article aims to explore the effectiveness of positive reinforcement in EFL (English as a foreign language) classrooms with the situations of enhancing the learnability of EFL learners. For the concern, I applied positive reinforcement to one section of class 11 for a month, and to another section of the same class, there was no treatment after the treatment post-test was administered in the two groups. From the data, the group in which the treatment applied was found better motivation in learning; as a result, they can enhance learnability and develop a friendly situation in learning English. Therefore, positive reinforcement enhances the learnability of the learners, and they can develop the level of confidence, the horizon of knowledge, and cooperative learning strategies in the EFL situation.